Mengatasi Kekerasan Verbal Pada Anak di Sekolah: Upaya Perlindungan Hukum Yang Efektif - M. Fatkhur Rokhman (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Education is an opportunity or place for children’s future to get a decent life. In general, education can be interpreted as a process to develop themselves for individuals to carry out their lives. Verbal abuse in the school environment can occur anytime and anywhere. That way the school is a place to support children to study, values, politeness, honesty, good ethics in children. Violence against children can be in the form of physical violence or verbal violence. Researchers focused on the study of verbal violence that is commonly found in school units where we often know that verbal violence can be in the form of rude speech, yelling, defamatory, threatening, and insulting. So that it can cause trauma or psychological health to the child. Researchers conduct research using several relevant sources or literature studies sourced from journals, books, and articles to be studied using qualitative research methods that are analyzed in a normative descriptive manner.